The Effectiveness of Project-Based Learning and Problem-Based Learning in Improving Student Achievement and Involvement in Learning Mathematics - Hussein, Saddam; Khoiruzzadittaqwa, Muhammad; Luthfiyah, Luthfiyah; Alhaq, Muhammad Miftah (International Journal of Mathematics and Mathematics Education (IJMME), 2024)
This research examines the effectiveness of Project-based Learning (PjBL) and problem-based learning (PBL) in improving the involvement and achievements of students from elementary to high school. Using the Systematic Literature Review (SLR) method, we reviewed studies published from 2018 to 2023. The analysis results show that PjBL and PBL positively impacted students' cognitive, affective, and psychomotor aspects, facilitating active, collaborative, and independent learning. The use of interactive media in PjBl and PBL has been proven to increase student involvement in learning mathematics. This research contributed to developing effective mathematics teaching strategies at the elementary school level. It offered insights into using PjBL and PBL as alternative models that improve learning outcomes. Integrating interactive media in mathematics learning promises a deeper understanding of concepts, supporting educational practitioners and policymakers in designing innovative curricula and learning strategies for the future.